Clinical Assessment of Dental Implants Placed in Low-Quality Bone Sites Prepared for the Healing Chamber with Osseodensification Concept: A Double-Blind, Randomized Clinical Trial - Rafael Coutinho Mello-Machado; Carlos Fernando de Almeida Barros Mourão; Kayvon Javid; Henrique T. Ferreira; Pietro Montemezzi; Mônica Diuana Calasans-Maia; Plinio Mendes Senna (Applied Sciences, 2021)
The present study aimed to compare the stability of dental implants placed in low-quality bone prepared for the healing chamber with osseodensification technique and a standard undersized drilling. Sixteen subjects presenting D3 or D4 bone density according to Misch’s classification were randomly distributed to receive dental implants following either osseodensification (G1: n = 29) or standard undersized drilling (G2: n = 26) preparation techniques. Implant insertion torque (IT) and implant stability quotient (ISQ) were measured immediately after implant placement. Implant survival and secondary stability (ISQ) were evaluated after six months. The G1 group showed higher IT (39.0 ± 6.4 Ncm) than G2 (32.0 ± 3.4 Ncm) (p < 0.001). ISQ values were similar (p > 0.05) at the implant insertion (67.1 ± 3.2 and 65.5 ± 2.7 for G1 and G2, respectively). After six months healing, implant survival was equally comparable in both groups (p > 0.05), and ISQ values were higher than those of implant insertion (p < 0.001) but similar (p > 0.05) for both groups (74.0 ± 3.6 and 73.3 ± 3.2 for G1 and G2, respectively). Within the limitations of this study, the present RCT demonstrated that a wider surgical bed prepared by osseodensification instrumentation allowed for the bone healing-chamber concept in low-quality bone without any reduction in implant stability and success rate.